Application PAK RT Based Website Canva As Learning Media for Islamic Religious Education for Grade IV Elementary School - Diva Aura; Muhammad Reihanul Ilham; Yasmin Shabirah; Ani Nur Aeni (Prodi PGMI STIT Sunan Giri Bima, 2026)
Islamic Religious Education (PAI) learning in elementary schools often faces problems such as low student participation due to traditional teaching methods that make it difficult to access abstract materials. This study aims to develop an innovative learning medium in the form of a website-based application called